The effect of Trichoderma spp. against germination speed of batok glutinous rice seeds (Oryza sativa L. var. glutinosa) - Wibi m Syofian; Azwir Anhar (Bioscience, 2022)
Batok glutinous rice especially local varieties, is one of the agricultural commodities that can be used as a source of food. Besides having a good taste, batok glutinous rice is also not easily attacked by pests and rice seeds easily obtained. However, obstacles in the utilization of glutinous rice for local varieties are long harvest time and low production. Therefore, seed priming is carried out by utilizing biofertilizer derived from the rhizosphere fungus, Trichoderma spp. Trichoderma is a function that is classified as Plant Growth Promoting Function (PGPF) which is able to stimulate plant growth by producing growth regulators. This study aims to determine the response of the germination of batok glutinous rice seeds against of Trichoderma spp.This research is an experimental study using a completely randomized design with 7 treatments and 3 replications. The treatment given was soaking seeds with 6 types of Trichoderma spp. isolates and 1 control soaked with aquadest. The data obtained were analyzed statistically using ANOVA. If there are significant differences, further tests of DMRT are carried out with α = 5%.The results obtained indicate that Trichoderma spp. no significant effect on the percentage of germination and vigor index, but significant effect on the germination speed with RE isolates is the best isolate in increasing the seed germination speed.Beras ketan Batok khususnya varietas lokal, merupakan salah satu komoditas pertanian yang dapat dimanfaatkan sebagai sumber pangan. Selain memiliki rasa yang enak, beras ketan batok juga tidak mudah terserang hama dan bibit padi mudah didapatkan. Namun kendala dalam pemanfaatan beras ketan untuk varietas lokal adalah waktu panen yang lama dan produksi yang rendah. Oleh karena itu, priming benih dilakukan dengan memanfaatkan pupuk hayati yang berasal dari cendawan rizosfer Trichoderma spp. Trichoderma merupakan fungsi yang tergolong Plant Growth Promoting Function (PGPF) yang mampu merangsang pertumbuhan tanaman dengan memproduksi zat pengatur tumbuh. Penelitian ini bertujuan untuk mengetahui respon perkecambahan benih ketan batok terhadap Trichoderma spp. Penelitian ini merupakan penelitian eksperimen dengan menggunakan rancangan acak lengkap dengan 7 perlakuan dan 3 ulangan. Perlakuan yang diberikan adalah perendaman benih dengan 6 jenis Trichoderma spp. isolat dan 1 kontrol direndam dengan aquadest. Data yang diperoleh dianalisis secara statistik menggunakan ANOVA. Jika terdapat perbedaan yang signifikan, selanjutnya dilakukan uji DMRT dengan = 5%. Hasil yang diperoleh menunjukkan bahwa Trichoderma spp. tidak berpengaruh nyata terhadap persentase daya berkecambah dan indeks vigor, namun berpengaruh nyata terhadap kecepatan berkecambah dengan isolat RE merupakan isolat terbaik dalam meningkatkan kecepatan berkecambah benih.